Swinging into art with pendulum paintings. (2nd October 2018) - Taylor, Amy R.; Maurer, Stacey
Abstract: Children are captivated with how things work and they like to build things and in many ways, engineering comes naturally for them. Progress does not come from technology alone but from the melding of technology and creative thinking through art and design. There has been a push for STEAM-based curricula to be included in science classrooms and the Next Generation Science Standards (NGSS) provides the framework for integrating engineering design into the structure of science education. The push for the STEAM platform is derived from the lack of creativity and innovation in recent college graduates in the United States. This STEAM-based unit meshes engineering design, representing and interpreting data, visual arts, and motion/stability. As students investigated and analyzed pendulum motion, they also created unique pendulum paintings. Throughout this unit our students applied their content knowledge across several disciplines and in turn allowed them to gain a better understanding and retention of these concepts. Through creating their own pendulum paintings, the students learned about pendulums and how they work, designed and constructed their own pendulums, and applied prior knowledge of forces and motion in a controlled experiment.